The role of translation in teaching modern foreign languages - Moreira, Glauber Lima (Universidade Estadual Paulista, 2017)
This interview with Professor Dr. Janet DeCesaris, researcher of the department in Translation and Language Sciences from the Universitat Pompeu Fabra (UPF) and she is currently the principal of the Institut Universitari de Lingüística Aplicada (IULA), aims to present her contact with translation and her conception about the use of translation in the teaching of modern foreign languages in the current context.